Study of physical and mechanical properties of oil palm empty fruit bunch fiber reinforced polypropylene composites - Abu Saleh, Ahmed; M.A., Alam; A., Piee; M.R., Rahman; S., Hamdan (Universiti Tenaga Nasional, 2010)
The physical and mechanical properties of oil palm empty fruit bunch (OPEFB) reinforced polypropylene (PP) matrix composites with different fiber loading (10, 15, 20, 25, and 30 wt%) have been studied. Two different type of chemical treatments namely oxidized sodium periodate oxidation and urea coupling reaction has been used to improve the properties of the composites. In the current research, OPEFB fiber reinforced PP composites were manufactured using high voltage hot compression technique. Scanning electron micrographs of the fractured surfaces were taken to study the fiber/matrix interface adhesion. Reduced fiber agglomeration and improved interfacial adhesion was observed under scanning electron microscope in the case of oxidized OPEFB fiber and improved the compatibility in the case of urea treated oxidized OPEFB fiber reinforced PP composites. Tensile and flexural modulus significantly increased with fiber loading. However, tensile and flexural strength are found decreased beyond 25% by weight fiber loading. Effect of water absorption on the composites was also observed and it was found that oxidized OPEFB fiber reinforced PP composites absorbed less water compared to raw and urea treated oxidized OPEFB fibers reinforced PP composites. Overall, chemically treated OPEFB fiber reinforced PP composites showed better fiber/matrix interactions as observed from the good dispersion of fibers in the matrix system. Unlike the untreated OPEFB fiber reinforced PP composites, all treated OPEFB fiber reinforced composites had the same tendency of increasing the mechanical properties of composites.